2014
DOI: 10.4081/mi.2014.5354
|View full text |Cite
|
Sign up to set email alerts
|

Art therapy: an underutilized, yet effective tool

Abstract: Art therapy has been recognized as beneficial and effective since first described by Adrian Hill in 1942. Even before this time, art therapy was utilized for moral reinforcement and psychoanalysis. Art therapy aids patients with, but not limited to, chronic illness, physical challenges, and cancer in both pediatric and adult scenarios. Although effective in patient care, the practice of art therapy is extremely underutilized, especially in suburban areas. While conducting our own study in northeastern Ohio, US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 1 publication
0
12
0
2
Order By: Relevance
“…(We note that this by no means implies that art therapy is better than other forms of therapy, which can also have unique and powerful benefits; for instance, in robotics, some studies using Paro and KiliRo have reported success in reducing stress and psychologically helping elderly and children with autism [13][14][15].) Art therapy has been used with both adults and children for various conditions, including dementia, autism, depression, trauma (post-traumatic stress disorder, sexual abuse, and traumatic brain injury), AD/HD, schizophrenia, bipolar disorder, borderline personality disorder, AIDS, asthma, burns, cancer, chemical dependency, hemodialysis, sickle cell disease, and tuberculosis [6,[16][17][18][19].…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…(We note that this by no means implies that art therapy is better than other forms of therapy, which can also have unique and powerful benefits; for instance, in robotics, some studies using Paro and KiliRo have reported success in reducing stress and psychologically helping elderly and children with autism [13][14][15].) Art therapy has been used with both adults and children for various conditions, including dementia, autism, depression, trauma (post-traumatic stress disorder, sexual abuse, and traumatic brain injury), AD/HD, schizophrenia, bipolar disorder, borderline personality disorder, AIDS, asthma, burns, cancer, chemical dependency, hemodialysis, sickle cell disease, and tuberculosis [6,[16][17][18][19].…”
Section: Motivationmentioning
confidence: 99%
“…To recognize a person's emotion, we used a typical 14 channel wireless EEG with a sampling rate of 128 SPS; the Emotiv Epoc+. Electroencephalography (EEG) signals were obtained from four channels (AF3, F3, F4 and AF4) on the frontal lobe, and filtered into three bands using the Remez exchange algorithm, which iteratively finds a filter minimizing the maximum error in the desired frequency ranges [169]: Theta (4-8 Hz), Alpha (8)(9)(10)(11)(12) and Beta (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Mean log-transformed brain wave power values were computed for each of the four channels and three bands by extracting the spectral densities via Welch's method [170]: this involved averaging periodograms obtained using the Discrete Fourier Transform in Equation (1) on overlapping segments of the signal to reduce variance.…”
Section: Inferencementioning
confidence: 99%
“…Another intervention that can facilitate improvement of mental and emotional conditions due to stigma is art therapy. Art therapy is recognized as an effective tool for enhancing communication and self-esteem [5]. One form of art therapy that has been used to help PLHIV tell their stories is body mapping, which was originally conducted in South Africa [28].…”
Section: Introductionmentioning
confidence: 99%
“…Con una vasta referencia dentro de investigaciones tanto cuantitativas como cualitativas (Bitonte & De Santo, 2014;Drake & Hodge, 2015;Drake, Coleman & Winner, 2011;Hacking, Secker, Spandler, Kent & Shenton, 2008), se puede incluso considerar como un aspecto psicológico modificable mediante este tipo de intervención. A pesar de ello, la forma como sucede este proceso no es explorado.…”
Section: Introductionunclassified